Syair Wasf al-Qalb Karya Ibn Qayyim al-Jauziyyah - Wardani, Yani'ah (Buletin Al-Turas, 2009)
Ibn Qayyim al-Jauziyyah who had skilss in multidisciplinary sciences was promient scholar in IslamÂ  in the Middle Ages. Besides an expert in the fiqh (islamic jurisprudence) of Hambali School of thoughts, he was also expert in Hadis, theologian of Salafi School of thoughts, psychologist, and expert in Arabic languege and literature. One of his works in Arabic languege and literature. One of his works in Arabic language and literature was Qasidah Mimiyah and Qosidah Nuniyah wich consist of numerous poems. one of the poems is was al-Qalb (description of the heart). Expert in Arabic literature stated that the poem was alQalb is invaluable in the works of litarature as it fulfiills the element of critic of literature, such as : firstly the element of feeling (atifah/emotion), secondly the element of imagination (khayal/imagination), thirdly the element of idea (fikrah/idea) and fourtly the element of languege style (uslub/surah/style)